Wireless Technology, Intelligent Network Technologies, Smart Services and Applications Proceedings of 4th International Conference on Wireless Communications and Applications (ICWCA 2020) - Jain, Lakhmi C.; Kountchev, Roumen; Hu, Bin.; Kountcheva, Roumiana; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers selected papers presented at the 4th International Conference on Wireless Communications and Applications (ICWCA 2020), held at Hainan University, China. The second volume will involve research works aimed at the contemporary applications: emerging wireless/mobile applications, context and location-aware wireless services; wireless telemedicine and e-health services; intelligent transportation systems; RFID technology and application; cognitive radio and sensor-based applications; content distribution in wireless home environment and many others.
Design and Implementation of In-depth Investigation Service System for Road Transportation Safety Accidents Based on Micro-service Architecture -- Research on Video Information Superimposition and Interaction Method Oriented to Disaster Emotional Knowledge of Power Grid -- The Design and Implementation of the Bidding Strategy in the Dou Dizhu Game -- Research on the Evaluation of (3z(BSpecial Delivery Classroom(3y (Bto Promote the Children Development in Weak Rural Schools -- Research on the Map Construction of SLAM Mobile Robot Based on the Two-dimensional Code Correction -- Research on Intelligent Security System of Online Car Based on Computer Vision -- Research on the Design of Mobile APP Product$1 (BTaking$1 (BWei Weather$1 (BAPP as an Example -- A Low-Complexity Tensor Completion Scheme Combining Matrix Factorization and Smoothness -- DOA Tracking with Multi-Bernoulli Filter for Two Parallel Linear Array: Reconstruct MUSIC as Pseudo-Likelihood -- Fuzzy-ADRC Strategy to DFIG Low Voltage Ride Through.s
Keywords: Wireless communication systems; Mobile communication systems; Internet of things; Telecommunication; Computational intelligence; Wireless and Mobile Communication; Internet of Things; Communications Engineering, Networks; Computational Intelligence; Wireless communication systems -- Congresses